Suárez et Kant. Histoire et devenir humain - Coujou, Jean-Paul (Revue des sciences philosophiques et théologiques, 2024)
For both Suarez and Kant, the question of man’s place in the universe is inextricably linked to his moral destiny, i.e. to an end that can only be conceived as the outcome of rational will and human freedom. History confirms man’s unique place in creation as a practical being who assigns to the universe a final goal that it is up to him to achieve, and of which peace represents an inescapable moment, whether thought of from a ruse of nature for Kant, or from an eschatological perspective of salvation for Suarez. History means, in and through finitude, that the universe requires man, as a free and rational creature, to assign him a final goal, modifying himself and nature to achieve it. From then on, cosmopolitanism must attest to the interweaving of politics and finitude, translating into human destiny the de facto division between what man ontologically is, and what he ethically must be.